(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
Fabrics modified with the participation of ammophos as a catalyst gave high levels of crease resistance with the least loss of initial strength and a stable size, which indicates the high efficiency of this catalyst